Comparative effect of different strategies for the screening of lung cancer: a systematic review and network meta-analysis. - Chen, Yancong; Zhang, Zixuan; Wang, Huan; Sun, Xuemei; Lin, Yali; Wu, Irene X. Y. (Journal of Public Health: From Theory to Practice (2198-1833), 2022)
Aim: The largest-ever European randomized controlled trial (RCT) compared low-dose computed tomography (LDCT) with usual care for lung cancer screening and reported the mortality results in 2011. Therefore, we conducted this network meta-analysis (NMA) to update the evidence. Subject and methods: Three electronic databases were searched for potentially eligible RCTs. Pairwise meta-analyses and NMA were conducted. Results: Eleven RCTs were finally included. Results from pairwise meta-analysis showed that when compared with usual care, LDCT reduced lung cancer mortality (pooled relative risk [RR]: 0.79; 95% confidence interval [CI]: 0.69–0.90), but not all-cause mortality (pooled RR: 0.95; 95% CI: 0.90–1.01). NMA showed differences between LDCT and usual care (pooled RR: 0.85; 95% credible interval [CrI]: 0.72–0.97) in reducing lung cancer mortality. No statistically meaningful difference was found in terms of all-cause mortality reduction (LDCT vs. usual care: pooled RR: 0.97; 95% CrI: 0.91–1.02). LDCT showed the highest probability of being the most effective screening strategy in terms of mortality reduction. Conclusion: LDCT showed a statistically significant effect in reducing long-term lung cancer mortality when compared with usual care in lung cancer screening. It also showed a promising absolute effect in reducing all-cause mortality, although no statistical difference was observed. Further studies are needed to explore population-specific optimal screening strategies.